2013
DOI: 10.3109/10253890.2013.777702
|View full text |Cite
|
Sign up to set email alerts
|

Acute psychological stress increases peripheral blood CD3+CD56+natural killer T cells in healthy men: possible implications for the development and treatment of allergic and autoimmune disorders

Abstract: Acute psychological stress has primarily been investigated regarding its effects on conventional lymphocytes such as natural killer (NK) cells and CD4(+) and CD8(+) T cells. However, it might be important to focus on more "specialized" lymphocyte subsets, playing a role, for instance, in allergic conditions and autoimmunity, to identify links between stress, the immune system and somatic diseases. Using flow cytometry we determined frequencies of circulating T helper (Th)1-type (CD226(+)) and Th2-type (CRTH2(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Transport stress significantly increased the cells under investigation. Similarly, an increase in CD4+ and CD8+ cells has also been reported in poultry (Han et al 2010), mice (Satoh et al 2006), pigs (Qiongxia et al 2009) and humans (Atanackovic et al 2013) exposed to stress. Therefore, an increase in these cells due to transport stress was expected.…”
Section: Discussionmentioning
confidence: 70%
“…Transport stress significantly increased the cells under investigation. Similarly, an increase in CD4+ and CD8+ cells has also been reported in poultry (Han et al 2010), mice (Satoh et al 2006), pigs (Qiongxia et al 2009) and humans (Atanackovic et al 2013) exposed to stress. Therefore, an increase in these cells due to transport stress was expected.…”
Section: Discussionmentioning
confidence: 70%
“…This also seems to influence more robust immune response upon repeated stimulation with the same antigen months later . This can be beneficial in cases when increased immunoprotection is needed, but detrimental in the cases of immunopathology such as allergic conditions and autoimmune disease (Atanackovic et al 2013;Dhabhar 2009;Dhabhar and Viswanathan 2005).…”
Section: Stress and The Immune Systemmentioning
confidence: 99%
“…Catecholamines and cortisol suppress IFN- production [31] and it was unlikely that the increased concentrations observed were a result of an endocrine stimulus. That being said, Atanackovic et al using an acute psychological stress model found increased concentrations of T cells in peripheral circulation following the stress challenge [36]. That same study found no change in circulating iNKT cells [36].…”
Section: Peripheral Immune Response To Trainingmentioning
confidence: 99%
“…That being said, Atanackovic et al using an acute psychological stress model found increased concentrations of T cells in peripheral circulation following the stress challenge [36]. That same study found no change in circulating iNKT cells [36]. Other work has shown T cells to be stress responsive lymphocytes mobilized following either psychological or exercise stress in a dose-dependent manner correlated with cardiac activation and exercise intensity [37].…”
Section: Peripheral Immune Response To Trainingmentioning
confidence: 99%